2024
DOI: 10.1002/ctm2.1548
|View full text |Cite
|
Sign up to set email alerts
|

Molecular features of luminal breast cancer defined through spatial and single‐cell transcriptomics

Ryohei Yoshitake,
Hitomi Mori,
Desiree Ha
et al.

Abstract: BackgroundIntratumour heterogeneity is a hallmark of most solid tumours, including breast cancers. We applied spatial transcriptomics and single‐cell RNA‐sequencing on patient‐derived xenografts (PDXs) to profile spatially resolved cell populations within oestrogen receptor‐positive (ER+) breast cancer and to elucidate their importance in oestrogen‐dependent tumour growth.MethodsTwo PDXs of ‘ER‐high’ breast cancers with opposite oestrogen‐mediated growth responses were investigated: oestrogen‐suppressed GS3 (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…These include the cell lines used in the long-term estrogen deprivation studies. In addition, the only two estrogen-suppressed patient-derived xenograft models reported to date, WHIM16 [ 13 ] and GS3 [ 14 ], are both luminal B cell lines [ 15 , 16 ], suggesting that the apoptotic pathway triggered by estrogen has been elucidated exclusively in luminal B cells. The story might therefore be different in Luminal A cells.…”
Section: Estrogen-induced Regression In Er+ Cancersmentioning
confidence: 99%
“…These include the cell lines used in the long-term estrogen deprivation studies. In addition, the only two estrogen-suppressed patient-derived xenograft models reported to date, WHIM16 [ 13 ] and GS3 [ 14 ], are both luminal B cell lines [ 15 , 16 ], suggesting that the apoptotic pathway triggered by estrogen has been elucidated exclusively in luminal B cells. The story might therefore be different in Luminal A cells.…”
Section: Estrogen-induced Regression In Er+ Cancersmentioning
confidence: 99%
“…This high-plex spatially resolved RNA detection allows for transcriptomic characterization in spatially distinct areas. Some spatial transcriptomic studies have recently been reported in breast carcinoma (15)(16)(17)(18); however, only a few studies have analyzed the differences in gene expression between age groups of patients with HRpositive breast carcinoma. This study aimed to analyze the spatial transcriptomic profiles of younger and older patients with HR-positive breast carcinoma using DSP technology.…”
mentioning
confidence: 99%